Criminal justice in an age of populism: Introduction to the Special Issue: Karanie w czasach populizmu. Wprowadzenie do Numeru Specjalnego (Archives of Criminology, 2023)
The rise of populism, as a by-product of neoliberal policies in Western democratic societies, became a hallmark feature of the supposed end-of-history era and post-cold-war order. Surprisingly, that shift was also evidenced in post-communist “new” democracies in Central and Eastern Europe. The field of criminal justice became one of the core areas of populist discourse. Penal populism indeed became a way to address concerns and fears that emerged in other realms. A Free-Market economy, immigration, the decline of the welfare state opened up huge social divisions and in the form of previously undreamt of levels of wealth for some, nothing but uncertainty and insecurity amidst poverty and crime fears for many more. Mass immigration from poorer regions challenged our cultural identity for both individuals and the nation state itself, which notion had been put at risk. Local contingencies also play an important role in this, of course. In some societies, versions of Christian values have joined populist forces in targeting women’s rights or those of the LGBT community. Penal populism has reshaped how it was possible to think about criminal justice. This includes the abandonment of previous restraints on imprisonment in both old and new democracies. Nevertheless, the liberal democratic model of criminal justice may also have two unlikely saviours of its own. One of these may be the COVID virus itself. The successful antidote to this involves trust in scientific knowledge. The successful antidote to COVID involves trust in scientific knowledge and expertise; high levels of trust in a strong central government, greater trust in public broadcasting organisations, and much stronger, social cohesion rather than the divisions that populism thrives on. The second unlikely saviour may be Vladimir Putin. With his war against the Ukraine state and its people, we also see what might be next in the route that populism is following: a form of autocracy; denial of free speech and all liberal values, killings of political opponents and the total defenseless and helplessness of individuals in front of the state apparatus of power.